2007
DOI: 10.1002/dvdy.21125
|View full text |Cite
|
Sign up to set email alerts
|

Functional expression of aquaporins in embryonic, postnatal, and adult mouse lenses

Abstract: Aquaporin 0 (AQP0) and AQP1 are expressed in the lens, each in a different cell type, and their functional roles are not thoroughly understood. Our previous study showed that these two AQPs function as water transporters. In order to further understand the functional significance of these two different aquaporins in the lens, we investigated their initiation and continued expression. AQP0 transcript and protein were first detected at embryonic stage (E) 11.25 in the differentiating primary fiber cells of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
67
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(77 citation statements)
references
References 67 publications
9
67
1
Order By: Relevance
“…Mip transcripts and Mip protein were first detected at E11 in the differentiating primary fibre cells; its synthesis continued through the adult stage in the secondary fibre cells [85]. The human MIP gene is located on chromosome 12q13, and Berry et al [86] identified two dominant mutations (G134E and T138R) leading to polymorphic and lamellar cataract.…”
Section: Genes Causing Juvenile Cataractmentioning
confidence: 99%
“…Mip transcripts and Mip protein were first detected at E11 in the differentiating primary fibre cells; its synthesis continued through the adult stage in the secondary fibre cells [85]. The human MIP gene is located on chromosome 12q13, and Berry et al [86] identified two dominant mutations (G134E and T138R) leading to polymorphic and lamellar cataract.…”
Section: Genes Causing Juvenile Cataractmentioning
confidence: 99%
“…MIP/AQP0 water channels show different properties from those formed by AQP1 in either endogenous or exogenous functional assays. MIP/AQP0 water channels, besides functioning with lower efficiency than those formed by AQP1, are Hg 2+ -insensitive and pH-dependent, whereas AQP1 channels are inhibited by Hg 2+ and are pH-independent (Mulders et al 1995;Nemeth-Cahalan and Hall 2000;Varadaraj et al 1999Varadaraj et al , 2005Varadaraj et al , 2007.…”
Section: **mentioning
confidence: 97%
“…4a (Varadaraj et al 2005(Varadaraj et al , 2007. MIP/AQP0 water channels show different properties from those formed by AQP1 in either endogenous or exogenous functional assays.…”
Section: **mentioning
confidence: 98%
See 2 more Smart Citations